International terrorism and threats to security managerial and organizational challenges - Burke, Ronald J.; Cooper, Cary L. (New horizons in management, 2008)
The book reviews events since 9/11, which sets the foundation for the rest of the book. It scrutinizes the central role of governments as targets, agents and protectors of citizens, then considers the impact of terrorism on people and organizations based on research evidence from the US, Spain, and Israel. The authors examine how to increase individual coping resources, maintain work motivation in trying times and develop worksite emergency procedures. They also identify the key qualities of organizations that were able to recover quickly following devastating loss.